2007
DOI: 10.3928/1081-597x-20070501-14
|View full text |Cite
|
Sign up to set email alerts
|

Limbal Relaxing Incisions to Correct Corneal Astigmatism During Phacoemulsification

Abstract: PURPOSE: To evaluate the safety and efficacy of limbal relaxing incisions for the correction of corneal astigmatism during phacoemulsification. METHODS: Fifty eyes of 37 patients (mean age 66.5 years, range: 45 to 80 years) with cataract and coexisting topographic astigmatism were included in the study. Eyes were randomly divided into two groups: eyes that underwent cataract surgery with limbal relaxing incisions (cataract LRI group) and eyes that underwent cataract surgery only (control group). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…The undercorrection of the preexisting keratometric astigmatism by LRIs in our study is consistent with that in previous studies. [4][5][6][7] With regard to the stability of LRIs over time, we found that from 2 to 10 weeks after surgery, there was a statistically significant decrease in SIA overall (PZ.002) and in the WTR subgroup (PZ.004). In the ATR subgroup, there was also a decrease in SIA from 2 to 10 weeks, although it did not reach statistical significance (PZ.1).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The undercorrection of the preexisting keratometric astigmatism by LRIs in our study is consistent with that in previous studies. [4][5][6][7] With regard to the stability of LRIs over time, we found that from 2 to 10 weeks after surgery, there was a statistically significant decrease in SIA overall (PZ.002) and in the WTR subgroup (PZ.004). In the ATR subgroup, there was also a decrease in SIA from 2 to 10 weeks, although it did not reach statistical significance (PZ.1).…”
Section: Discussionmentioning
confidence: 82%
“…Some studies found the effects of LRIs regress over time, 4,7,9,11,12 while others found the effects to be stable. 5,6,[13][14][15][16] Furthermore, in general, published studies of LRIs in cataract surgery had a mean follow-up of 1 year or less with the exception of 2, which had a mean follow-up of 17 months 4 and 3 years. 12 In both studies, the authors describe a mild regression of the effects of LRIs.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies [16][17][18][19] used different nomograms to correct astigmatism during cataract surgery, and they report frequent undercorrection. In our study, only 4 eyes (5.5%) had overcorrection and all were in women older than 70 years.…”
Section: Discussionmentioning
confidence: 98%
“…Moderate amounts (!2.0 D) of corneal astigmatism have traditionally been addressed through peripheral corneal relaxing incisions or judicious selection of incision site. [3][4][5] The introduction of the AcrySof toric IOL (Alcon Laboratories, Inc.) provided a new method for correcting corneal astigmatism in pseudophakic patients. 6 The IOL can be readily oriented in the eye and has shown excellent postoperative stability, with 95% of IOLs within 10 degrees of the intended axis of implantation 6 months after surgery.…”
mentioning
confidence: 99%